(untitled) (ModaPalavra e-periódico, 2009)
This essay intends to analyze the aspects of the stylistís creation process as creator of authorial fashion, as well as pointing out the stylist/authorís identity, his/her cultural and social universe to outline his/her creation. In this study the participation of the fashion user will be involved that, after the launching of a collection, acts in a process of resignification and reorganization of the paraded parts and that, finally, culminates in the recriation of the parts aiming at the maintenance of the personal style of this user, its form to express ideas. The article also intends to bring up the process of alterization originated from the creation of a authorial fashion collection and its effects on consumers.